Analisis Perbedaan Harga Saham Antara Sebelum dan Sesudah Pandemi Covid-19 - Dita Dwi Febriani; Azib Asroi (UNISBA Press, 2022)
ABSTRACT- This study aims to examine and analyze the difference in stock prices between before and after the Covid-19 pandemic. In early March 2020 there was an outbreak of a virus called the Covid-19 pandemic. The outbreak caused the Jakarta Composite Index (ISHG) to weaken. Issues surrounding the Covid-19 pandemic are very vulnerable to affecting the stock market. However, stock trading activities are still valid and carried out. The research method uses descriptive and verificative, data collection techniques through secondary data from the annual report. The research sample consisted of 30 companies in the financial, hotel and tourism, transportation, pharmaceutical, and retail sub-sectors listed on the Indonesia Stock Exchange (IDX), the sampling method used was purposive sampling. The results showed that descriptively the development of stock prices in the financial, hotel and tourism, transportation, and retail sub-sectors experienced fluctuations which tended to decrease between before and after the Covid-19 pandemic, while only stock prices in the pharmaceutical sub-sectors experienced fluctuations which tended to increase. between before and after the Covid-19 pandemic. The verificatively shows that there are significant differences between stock prices in the financial, hotel and tourism, transportation, pharmaceutical, and retail sub-sectors before and after the Covid-19 pandemic, this is obtained from hypothesis testing using the Paired Sample t-Test. Abstrak- Penelitian ini bertujuan untuk menguji dan menganalisis perbedaan harga saham antara sebelum dan sesudah pandemi Covid-19. Pada awal bulan maret tahun 2020 terjadi wabah virus yang disebut pandemi Covid-19. Adanya wabah ini menyebabkan Indeks Harga Saham Gabungan (ISHG) melemah. Isu seputar pandemi Covid-19 sangat rentan mempengaruhi bursa. Meski demikian, aktivitas perdagangan saham tetap berlaku dan dijalankan. Metode penelitian menggunakan deskriptif dan verifikatif, teknik pengumpulan data melalui data sekunder dari annual report. Sampel penelitian sebanyak 30 perusahaan pada sub sektor keuangan, hotel dan pariwisata, transportasi, farmasi, dan retail yang terdaftar di Bursa Efek Indonesia (BEI), metode pengambilan sampel menggunakan purposive sampling. Hasil penelitian menunjukan bahwa secara deskriptif perkembangan harga saham pada sub sektor keuangan, hotel dan pariwisata, transportasi, dan retail mengalami fluktuasi yang cenderung menurun antara sebelum dan sesudah pandemi Covid-19, sedangkan hanya harga saham pada sub sektor farmasi yang mengalami fluktuasi yang cenderung meningkat antara sebelum dan sesudah pandemi Covid-19. Adapun secara verifikatif menunjukkan bahwa terdapat perbedaan signifikan antara harga saham pada sub sektor keuangan, hotel dan pariwisata, transportasi, farmasi, dan retail sebelum dan pasca pandemi Covid-19, hal tersebut diperoleh dari pengujian hipotesis menggunakan Paired Sample t-Test.